An Intestine-Derived Neuropeptide Controls Avoidance Behavior in Caenorhabditis elegans - Kiho Lee; Eleftherios Mylonakis (Cell Reports, 2017)
Adjusting to a continuously changing environment is a key feature of life. For metazoans, environmental changes include alterations in the gut microbiota, which can affect both memory and behavior. The bacteriovorous nematode Caenorhabditis elegans discriminates between pathogenic and non-pathogenic food sources, avoiding the consumption of pathogens. Here, we demonstrate the role of the intestine in regulating C. elegans avoidance to Pseudomonas aeruginosa by an insulin-like neuropeptide encoded by ins-11. The transcriptional expression of ins-11 is controlled through transcription factor hlh-30 and the p38 mitogen-activated protein kinase (MAPK) pathway. ins-11 negatively controls signal pathways in neurons that regulate aversive learning behavior. Attenuation of ins-11 increased avoidance behavior and survival on pathogenic bacteria but decreased opportunities to find a food source as well as lowered energy storage and the number of viable progeny. Our findings support a role for the intestine in avoidance and identify an advantageous role for negative feedback that allows C. elegans to actively balance noxious and favorable environments.